Measurement of the azimuthal anisotropy for charged particle production in $\sqrt{s_{NN}}=2.76$ TeV lead-lead collisions with the ATLAS detector - ATLAS collaboration (3048 authors) (2012)
Differential measurements of charged particle azimuthal anisotropy are presented for lead-lead collisions at sqrt(s_NN) = 2.76 TeV with the ATLAS detector at the LHC, based on an integrated luminosity of approximately 8 mb^-1. This anisotropy is characterized via a Fourier expansion of the distribution of charged particles in azimuthal angle (phi), with the coefficients v_n denoting the magnitude of the anisotropy. Significant v_2-v_6 values are obtained as a function of transverse momentum (0.5<pT<20 GeV), pseudorapidity (|eta|<2.5) and centrality using an event plane method. The v_n values for n>=3 are found to vary weakly with both eta and centrality, and their pT dependencies are found to follow an approximate scaling relation, v_n^{1/n}(pT) \propto v_2^{1/2}(pT). A Fourier analysis of the charged particle pair distribution in relative azimuthal angle (Dphi=phi_a-phi_b) is performed to extract the coefficients v_{n,n}=<cos (n Dphi)>. For pairs of charged particles with a large pseudorapidity gap (|Deta=eta_a-eta_b|>2) and one particle with pT<3 GeV, the v_{2,2}-v_{6,6} values are found to factorize as v_{n,n}(pT^a,pT^b) ~ v_n(pT^a)v_n(pT^b) in central and mid-central events. Such factorization suggests that these values of v_{2,2}-v_{6,6} are primarily due to the response of the created matter to the fluctuations in the geometry of the initial state. A detailed study shows that the v_{1,1}(pT^a,pT^b) data are consistent with the combined contributions from a rapidity-even v_1 and global momentum conservation. A two-component fit is used to extract the v_1 contribution. The extracted v_1 is observed to cross zero at pT\sim1.0 GeV, reaches a maximum at 4-5 GeV with a value comparable to that for v_3, and decreases at higher pT.